Comparison of the clinical outcomes between short-term and long-term opioid users with noncancer pain at pain clinics - Abdullah Sani, Asween Rowena; Zin, Che Suraya (Wolters Kluwer - Medknow, 2020)
Introduction: The clinical use of opioids for long-term for noncancer pain indications remains a controversy. More studies are needed for evidence-based guidelines in noncancer pain management involving opioids. The primary objective of this study was to investigate the clinical outcomes of the short-term and long-term opioid use among patients with noncancer pain. Materials and Methods: This is a retrospective cross-sectional study where patients (aged ≥18 years) with noncancer pain treated with opioids were recruited from three pain clinics in Malaysia. Data on patients’ opioid use were collected from prescription records. The individual days covered with opioids per patient were calculated and based on this, patients were classified as short-term (<90 days) or long-term (≥90 days) opioid user. Outcome measures included pain intensity and pain interference with daily activities assessed by Brief Pain Inventory – Short Form (BPI-SF), health-related quality of life (HRQoL) assessed by 36-Item Short Form Health Survey version 2 (SF-36v2).These measures were compared between short-term and long-term opioid users.Results: Of the 61 noncancer pain patients recruited, 49.2% (n = 30/61) were shortterm and 50.8% (n = 31/61) were long-term opioid users. There were no statistically significant differences in the mean scores of pain intensity, pain interference with daily activities, and HRQoL between short-term and long-term opioid users in this study. Conclusion: Findings of this study imply that long-term opioid therapy does not provide significant pain relief or improvement in patients’ functional capability and HRQoL in noncancer pain patients. Future prospective studies with larger sample sizes are needed to support the findings of this study